This poster - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The World of Spore Readers (1). Summary report of the Uses of Spore Survey The World of Spore readers (compilers).This poster was produced by the Spore consortium of Louma productions and Médiateurs which compiles Spore for its publisher, CTA.The...